Perceptional differences in the factors of local acceptance of spent nuclear fuel repositories. (September 2017) - Kim, Taehyun; Park, Hyunjoo
Abstract: In the process of land use planning, massive social costs are incurred as various conflicts arise due to the location of locally unwanted land-use (LULU) such as spent nuclear fuel repositories. The factors affecting local acceptance of such facilities may vary according to individuals' perceptional differences. This study aims to examine the differences in factors affecting local acceptance in regards to residents' risk perception of spent nuclear fuel repositories. To do so, Q methodology was adopted. Three perceptional types—safety concerns-government distrust (type 1), safety trust-government trust (type 2), and safety concerns-conflict avoidance (type 3)—were identified and the differences in local acceptance factors among these types were verified via path analysis. The results showed that risk perception had the highest influence on local acceptance for types 1 and 3, whereas economic feasibility had the greatest influence for type 2. The methodology and results of this study may contribute to developing a policy on siting LULU facilities in consideration of local acceptance and the risk perception of residents.